(untitled) (Journal of the College of Basic Education, 2022)
The present study aims at: * Is the use of academic Programmed according to the visual perception of Basics Arabic font has any effect on students the Achievement of domestic education department in the material? For the purpose of verification of the objective of this research and then formulate the following null hypothesis:- There are no statistically significant differences at the level (05 0.0) between the average scores of students in the control and experimental groups in cognitive achievement in the post test of knowledge of Kufic square. There are no statistically significant differences at the level (05 0.0) between the average scores of students in the control and experimental groups in achievement in the post test skills in Kufic square. 3- There are no statistically significant differences between the average scores of the experimental group (taught according to the method of learning exploration) at the level of significance (0.05) in the pre and post test of knowledge. 4- There are no statistically significant differences at the level (050.0) between the average scores of students in the experimental group in the cognitively pterions and posttest. To validate these hypotheses the researcher conducted experiment lasted for an entire semester, The data is made from students of the first year department of family education and technical professions department - College of Basic Education Almustansiriya university. The number are(179) students, After the sample is selected and divided into two groups, The first group( the experimental) consists of(20) students ,and the second group the control group consists of (20) students for each of the experimental group and the control group and two groups in gender, number, age, previous experience and having identified the researcher topics of scientific material that will be examined during the duration of the experiment multiple topics, drafted researcher behavioral objectives, and prepared lesson plans to her, and offered to set of experts and specialists to rule on its validity, and carried out the necessary adjustments and became the plans ready for application in the light of the views. conclusions, including: - This strategy helps the learner in the use of information and knowledge and employs them in the positions of the various educations, and to achieve the best education to increase its ability to develop a way of thinking skills and positive trends towards the article Customize the courses are interested and focused on teaching aids and visual sensory faculties of basic education. Encouraging urged faculty members to find entrances to modern teaching of the curriculum based on the employment of the visual field in educational programs because of its significant role in learning. Held training sessions for faculty members at college’s basic education under the supervision of qualified instructors to introduce them to the programs and teaching aids visual and sensual. And how to set up and use in teaching. In light of this, the researcher developed a number of recommendations concerning the results of the research, including: - conduct studies on the impact of an educational program on the image according to the memory in the collection of students of family education and technical professions in the material line and decoration. Conduct studies on the impact of an educational program according learning foresight to collect students of family education and technical professions in the material calligraphy and ornamentation.